Legal Education For The Community Through The Upmi Faculty of Law Seminar On Consumer Protection In Digital Transactions and The Economy - Ismayani; Yusuf Hanafi Pasaribu; Winta Hayati; Yulkarnaini Siregar; Ridho Syahputra Manurung; Taufika Hidayati (International Journal Of Community Service, 2026)
The growth of digital transactions and the creative economy in Indonesia brings tremendous opportunities as well as significant legal risks. In reality, many people do not yet understand their rights as consumers and do not know what to do when they suffer losses. This situation serves as the background for the organization of the Seminar by the Faculty of Law of Universitas Pembinaan Masyarakat Indonesia (UPMI) Medan as part of its community service program. The seminar, themed Consumer Protection in Digital Transactions and the Creative Economy, was designed to provide practical understanding to the community, particularly students, regarding consumer protection regulations, legally guaranteed rights, challenges in the creative economy sector, and complaint channels available when their rights are violated. The methods employed included interactive lectures, panel discussions, and direct question-and-answer sessions with speakers competent in consumer law and the digital economy. Pre- and post-activity evaluations showed a significant increase in participants' understanding of Law No. 8 of 1999 on Consumer Protection, the Electronic Information and Transactions Law (ITE Law), the complaint mechanism through BPSK, and preventive measures in digital transactions. This activity is expected to be part of ongoing efforts to promote legal literacy in the digital era.